KNITTING MODULAR Shawls, Wraps, and Stoles - Leapman, Melissa; Steege, Gwen; Lumsden, Michal; Kolesar, Alison (North Adams, MA : Storey Publishing, 2018)
Shawls are practical, versatile, and an ever-popular project among knitters. Noted designer Melissa Leapman has developed an innovative technique that literally promises hundreds - even thousands - of beautiful shawl design options in this one book! Beginning with a simple triangular wedge, Leapman shows how multiple knit triangles can be joined together to create square, rectangular, trapezoidal, and semicircular shapes. Her easy and customisable technique offers knitters endless flexibility in design and yarn choices.
Includes index
Keywords: Knitting -- Patterns; Knitting -- Technique; Shawls